Membaca Borjuisasi Gaya Hidup Masyakarat Desa: Perspektif Meanings and Media Terhadap Film Pendek Pemean - Sunaryanto, Sunaryanto (INTERAKSI PERADABAN: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This research aims to analyze the meaning of the bourgeoisie of Yogyakarta village society as represented in the short film Pemean. The research method used is qualitative with a media studies and cultural studies paradigm. Data collection was carried out by literature review, documentation and observation of the short film Pemean. The data analysis method uses mass media textual analysis based on meanings and media theory, namely semiotics, denotation and connotation, structuralism, and code (myth and ideology). This research concludes that semiotically the short film Pemean contains signs of the village's natural environment, motorbikes, bicycles, brooms, rice. The social structure of Yogyakarta society today is no longer dominated by noble culture. Yogyakarta village society has shifted into a consumerist, bourgeois and capitalistic society. The motorbikes used by the community are a symbol of capitalism built by industry. Pemean (clothing clothes) and motorbikes, which are cultural symbols of village communities, are considered outdated and abandoned. Even though the social structure of Yogyakarta village society is still recognized as a center of culture, it is slowly but surely moving towards popular culture resulting from the industry of urban society. The people of Yogyakarta village no longer build a noble culture through agriculture because most of the people have changed their lifestyle to become bourgeois, driven by the power of capitalism.